Management as craft and developing craftership. Issue 1 (16th March 2022) - Ruth, Damian
Abstract : Purpose: The purpose of this paper is to offer an appraisal of the craft metaphor in management with particular reference to authority, resistance, care and the interior landscape of the manager/crafter. Design/method/approach: This is a conceptual essay that draws on an autoethnography. Findings: Respect for the limits of managerial and bureaucratic authority and an appreciation of the manager/crafter's interior landscape are crucial aspects of effective craft and management practice. Insights into the practice of craft may enhance understanding of how both craft and management are a potent brew of politics, power, people, history, reason, faith and authority and just how crucial the interior landscape of the manager/crafter is. Originality/value: This article offers a focus on an inadequately examined aspect of management/craft – the interior landscape of the manager – that is informed by an auto-ethnography and suggests a case for conceptualizing management as craft, with implications for management development.